Daisaikoto Prevents Post-dieting Weight Regain by Reversing Dysbiosis and Reducing Serum Corticosterone in Mice - Kawashima, Takanori; Ogata, Misaki; Fujita, Nina; Takahashi, Ryuji (Frontiers in Physiology, 2019)
Weight loss is often temporary and is generally followed by recurrent weight gain and a relapse of metabolic complications, whose severity may be even greater upon recurrence. Preventing recurrent obesity, understanding the control of the energy balance subsequent to weight loss, and reversing the predisposition to obesity are critical factors that warrant an in-depth study. Several Kampo medicines, including daisaikoto, have traditionally been used to manage obesity, but their mechanisms of action are not well studied and their effects on weight regain are unknown. Here, we investigated the therapeutic potential and mechanism of action of daisaikoto in a mouse model of recurrent obesity. The mouse model was established by feeding mice a high-fat diet, followed by a normal chow, and a second course of the high-fat diet. Daisaikoto inhibited not only obesity and regaining of weight post-dieting, but also dysbiosis, thereby overcoming the predisposition to obesity. Furthermore, we found that recurrent obesity or long-term consumption of the high-fat diet elevated serum glucose, insulin, and corticosterone levels, and that daisaikoto lowered serum cholesterol and free fatty acid levels. These results are consistent with the hypothesis that this medication may inhibit lipid absorption by inhibiting pancreatic lipase. However, daisaikoto had no effect on the body weight of lean mice fed a normal chow, suggesting that although this medicine prevents lipid absorption, it does not cause excessive weight loss. In conclusion, our results elucidate the mechanisms underlying daisaikoto activity, and suggest that it may serve as a safe and effective anti-obesity drug.